Intergroup reconciliation or social reconstruction: A scale for measuring social recovery after war - Čorkalo Biruški, Dinka (2009)
Once highly cohesive multi-ethnic communities that have gone through an atrocious conflict face great challenges of reconnecting destroyed social fabric. Our studies of social reconstruction processes in the city of Vukovar (Croatia) that was heavily destroyed during the 1991-95 war, show that in this previously well integrated multi-ethnic community division along ethnic lines is evident in many aspects of everyday life. Having in mind a controversial meaning of the concept of reconciliation, we organized our work around the concept of social reconstruction, defined as a process within and around a community which brings its damaged social functioning to an improved level of interpersonal and groups relations and renews the social fabric of the affected community (Ajdukovic, 2004 ; 2005). Based on Nadler’s (2002) concept of instrumental and socioemotional aspects of reconciliation and our own understanding of the post-war social reconstruction processes (Ajdukovic, 2004 ; 2005), Corkalo (2002), Ajdukovic & Corkalo (2004) and Corkalo Biruski & Ajdukovic (in press), we have constructed the Social Reconstruction Scale, containing a set of items that measure the following components: intergroup cooperation, intergroup empathy, intergroup trust, a need for apology, and intergroup forgiveness. A preliminary form of Social Reconstruction Scale with 50 items was administered to a sample of 150 young participants (mean age 23, 5 years), Croats and Serbs in the city of Vukovar. The item analysis resulted in a 21 item scale that was administered to the representative sample of adult Croats (N=210) and Serbs (N=123) aged from 18 to 65 years and living in the same city. Results for various aspects of social reconstruction differed in these two ethnic groups, depending on the degree of their victimization and reflecting differences in how they perceived their recent conflict and understand the possibilities for social recovery. The main finding however showed that there was no single underlying dimension that could be called reconciliation, and that captured all the aspects of the social recovery we measured: the five facets were interrelated, but with no single factor of higher order. Instrumental aspect of post-conflict social recovery, that we call cooperation was independent from the others, more emotional aspects of social relations tapped by the concepts of empathy, trust and the need for apology. They did not form a single higher order dimension either: a three-component model fit data much better, and showed an acceptable goodness of fit. We have called them factors of socioemotional approaching to the out-group. In sum, our data obtained in real settings, with groups with history of a real recent conflict do not support an idea that the reconciliation could be understood as two-dimensional concept: instrumental and socioemotional. Rather, our data showed that there are a few interrelated but relatively independent aspects of social recovery that describes the process of social reconstruction after the conflict.